Computational investigations on the hemodynamic performance of a new swirl generator in bifurcated arteries. Issue 4 (12th March 2019) - Prashantha, B.; Anish, S.
Abstract: Hemodynamic behaviour of blood in the bifurcated arteries are closely related to the development of cardiovascular disease. The secondary flows generated at the bifurcation zone promotes the deposition of atherogenic particles on the outer walls. The present study aims at suppressing the development of atherosclerosis plaque by inducing helical flow structure in the arterial passage. To realize this objective a novel swirl generator (stent like structure with an internal groove) has been developed to induce helicity in the bifurcated passage. The functional requirement of the swirl generator is to minimize the relative residence time (RRT) of the fluid layer near the endothelial wall without generating any additional pressure drop. Different configurations of the swirl generator have been tested computationally using large eddy simulation (LES) model. It is observed that the induced helical flow redistributes the kinetic energy from the centre to the periphery. A single rib swirl flow generator proximal to the stent treated passage can generate sufficient helicity to bring down the RRT by 36% without generating any additional pressure drop. The swirl flow adds azimuthal instability which increase vortex formations in the passage. The induced helical flow in the domain provokes more linked vortices, which may act as self-cleaning mechanism to the arterial wall.